Carnap and Quine: Analyticity, Naturalism, and the Elimination of Metaphysics. (6th October 2018) - Morris, Sean
Abstract: Rudolf Carnap is well known for his attack on metaphysics, and W. V. Quine is equally well known for his attack on Carnap's analytic/synthetic distinction. Receiving far less attention is their basic agreement that a properly scientific approach to philosophy should eliminate the metaphysical excesses of the past. This paper aims to remedy this. It focuses initially on the development of Carnap's rejection of metaphysics from 1932 to 1950 and the role that analyticity plays. It then turns to Quine, emphasizing his basic agreement with Carnap over the elimination of metaphysics and what this looks like without the analytic/synthetic distinction.